Leveraging Big Data in Pediatric Development Programs: Proceedings From the 2016 American College of Clinical Pharmacology Annual Meeting Symposium. Issue 1 (10th January 2018) - Mulugeta, Lily (Yeruk); Yao, Lynne; Mould, Diane; Jacobs, Brian; Florian, Jeffrey; Smith, Brian; Sinha, Vikram; Barrett, Jeffrey S.
Abstract : This article discusses the use of big data in pediatric drug development. The article covers key topics discussed at the ACCP annual meeting symposium in 2016 including the extent to which big data or real‐world data can inform clinical trial design and substitute for efficacy and safety data typically obtained in clinical trials. The current states of use, opportunities, and challenges with the use of big data in future pediatric drug development are discussed.